2009
DOI: 10.1165/rcmb.2008-0202oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-10 on Neutrophil Recruitment and Survival afterPseudomonas aeruginosaChallenge

Abstract: IL-10 is a potent, endogenous anti-inflammatory cytokine known to decrease cytokine and keratinocyte-derived chemokine (KC) expression. Traditionally, in vivo effects of IL-10 were extrapolated from studies employing systemic antibody neutralization. As a result, divergent data regarding the protective and/or harmful roles of IL-10 have been reported. In this study, we used a lung-specific, tetracycline-inducible IL-10 overexpression-transgenic (IL-10 OE) mouse to study the effects of IL-10 overexpression on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 35 publications
7
66
0
1
Order By: Relevance
“…In line with our observations, an early study using the RAW 264.7 macrophage cell line showed that IL-10 inhibited production of MIP-1 and MIP-2 after lipopolysaccharide stimulation (31). The impact of IL-10 on neutrophil recruitment was also studied by using a lung-specific, tetracycline-inducible IL-10-overexpressing transgenic mouse (32). It was found that during the early phase of Pseudomonas aeruginosa infection, neutrophil recruitment and cytokine (TNF-␣) and chemokine (KC) expres- sion were significantly decreased in the IL-10 transgenic mice, which resulted in impaired clearance of P. aeruginosa (32).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with our observations, an early study using the RAW 264.7 macrophage cell line showed that IL-10 inhibited production of MIP-1 and MIP-2 after lipopolysaccharide stimulation (31). The impact of IL-10 on neutrophil recruitment was also studied by using a lung-specific, tetracycline-inducible IL-10-overexpressing transgenic mouse (32). It was found that during the early phase of Pseudomonas aeruginosa infection, neutrophil recruitment and cytokine (TNF-␣) and chemokine (KC) expres- sion were significantly decreased in the IL-10 transgenic mice, which resulted in impaired clearance of P. aeruginosa (32).…”
Section: Discussionsupporting
confidence: 82%
“…The impact of IL-10 on neutrophil recruitment was also studied by using a lung-specific, tetracycline-inducible IL-10-overexpressing transgenic mouse (32). It was found that during the early phase of Pseudomonas aeruginosa infection, neutrophil recruitment and cytokine (TNF-␣) and chemokine (KC) expres- sion were significantly decreased in the IL-10 transgenic mice, which resulted in impaired clearance of P. aeruginosa (32). It has been shown previously that IL-10 reduces the stability of a number of mRNAs, including KC, TNF-␣, and MIP-1 (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of systemic IL-10 is determined by the timing of application and the underlying disease, whereby in states of sterile inflammation it may be beneficial but deleterious in infection. 30 In this study, we demonstrated that post-MI pulmonary edema engaged NK cells in an IL-10-mediated immunoregulatory circuit that functions to alleviate pulmonary edema.…”
Section: Circulation Research February 14 2014mentioning
confidence: 63%
“…Neutrophils are essential for host defense against P. aeruginosa and other bacterial infections of the lungs (32,(36)(37)(38). Neutropenic human patients (39,40) and laboratory mice (36,41,42) have enhanced susceptibility to pseudomonal pneumonia.…”
Section: High-affinity B 2 Integrins and Neutrophil Effector Functionmentioning
confidence: 99%